Self‐Reported Family Socioeconomic Status, the 5‐HTTLPR Genotype, and Delinquent Behavior in a Community‐Based Adolescent Population. Issue 1 (14th September 2012) - Åslund, Cecilia; Comasco, Erika; Nordquist, Niklas; Leppert, Jerzy; Oreland, Lars; Nilsson, Kent W.
<x xml:space="preserve">Abstract</x> Twin and adoption studies have demonstrated a significant contribution of both genetic and environmental factors to antisocial and delinquent behavior. Associations have been reported between the serotonin transporter (5‐HTT) and aggression, and between socioeconomic status (SES), aggression, and serotonergic functions of the brain. We aimed to investigate associations between the 5‐HTTLPR genotype and family SES in relation to delinquent behavior among adolescents. A total of 1, 467 17‐ to 18‐year‐old students in the county of Västmanland, Sweden, anonymously completed a questionnaire and gave a saliva sample. Family SES had a U‐shaped relation to delinquency, where adolescents with low and high family SES were the most delinquent. There were curvilinear interactions between the 5‐HTTLPR genotype and family SES in relation to delinquency. Among individuals having high family SES, boys with the LL (homozygous for the long allele) or LS (heterozygous) genotypes and girls with the SS (homozygous for the short allele) or LS (heterozygous) genotypes showed the highest delinquency scores. Among individuals having low family SES, boys with the LL (homozygous for the long allele) genotype and girls with the LS (heterozygous) genotype showed the highest delinquency scores. The present study suggests evidence for an interaction between family SES and the 5‐HTTLPR genotype in relation to juvenile delinquency. Aggr. Behav. 39:52‐63, 2013. © 2012 Wiley Periodicals, Inc.